Conselho estadual de assistência social: desafios e limites de sua atuação frente à gestão do suas no estado da Paraíba - Silva, Laerge Thadeu Cerqueira da (2015)
The National Social Assistance Policy has in recent years undergone significant changes in its structure and organization, where we experience and broadening their programs, services and technical policy management strategies, thereby consolidating the Single Social Assistance System (ITS) while Public Policy. Given this process, the Social Assistance Councils are very important role under the policy in view the need to increase opportunities for participation in society within the ITS. Thus, this work aims to conduct an analysis on the performance of the State Council of Social Service of Paraíba (CEAS) regarding state management ITS, with the parameter which sets the Basic Operational Norm of the Unified Social Assistance System 2012 (NOB ITS). Seek also to understand how the council has been working in the design, monitoring, evaluation and control of the resources of the Unified Social Assistance System in the State Paraíba. Therefore, we will as a working methodology to qualitative analysis of primary and secondary data collected from interviews with directors, reports, minutes, institutional documents and participation in meetings of collegiate and commissions. We hope with this, understand the various nuances of the CEAS acting under the control and co-management of Social Welfare Policy in the State. The role of councils in the ITS, is subject of great importance to be discussed, given the historical biases of social welfare policy, the need to overcome the patronage and paternalism and the complex relationship between the State and Civil Society.